Analisis Kebijakan Sistem Zonasi di SMP Negeri 31 Surabaya: Analysis of Zoning System Policy at SMP Negeri 31 Surabaya - Surya Bagus Kusuma, Pratama; Siswanto, Deny; Sufia, Rohana (Lembaga Bale Literasi, 2024)
The education equality program is one of the government's efforts to advance education in Indonesia through several policies, one of which is the policy of accepting new students through a zoning system. This zoning system emerged as a form of educational equality and to erase the image of superior schools that has spread in society. With this zoning system, it is hoped that all schools will have the same quality. Minister of Education and Culture Regulation Number 44 of 2019 contains the zoning system policy concerning acceptance of new students from Kindergarten to Senior High School/Vocational High School (SMA/SMK). This policy must be implemented in schools under the auspices of the Regional Government. With this new policy, it cannot be denied that many problems will arise for both the school and the community, namely students. This research aims to reveal the factual conditions of implementing the zoning system policy in accepting new students, especially at SMP Negeri 31 Surabaya, as well as to determine the impact of implementing this policy. This problem was analyzed using policy implementation theory according to George Edward III, namely communication, resources, disposition, and bureaucratic structure. This research method uses a qualitative approach. Data collection methods use interviews, documentation, and observation techniques. The results of this research reveal that communication between policy actors is carried out clearly and consistently, and outreach is carried out to the community. Human and non-human resources have supported all activities in implementing zoning system policies. The disposition in implementing the zoning system policy is excellent, which can be seen from the commitment and attitude of the implementing committee towards the policy. The bureaucratic structure in implementing the zoning system policy is very good, it can be seen from the division of tasks in the PPDB committee, that each committee has the task of accepting new students following standard operational procedures. Meanwhile, from the community or student perspective, different views emerged regarding this zoning policy, namely agreeing and disagreeing.